THE ASSESSING THE DISTRIBUTIONAL IMPLICATION OF VAT EXEMPTIONS OF EDUCATION AND HEALTH SECTORS - Marycha Puspitasari; Rus'an Nasrudin (DIA: Jurnal Administrasi Publik, 2024)
The tax revenues are still the primary state revenue sources in Indonesia. With the declining trend of corporate taxes, the challenge of increasing other taxes becomes even more severe, including Value Added Tax (VAT). The main change in the VAT provisions in the Law on the Harmonization of Tax Regulations is broadening the VAT basis. Among others are education and health services. This study aims to determine the effect of that policy combined with hypothetical reform on spending. Using micro simulation method and Susana’s data for March 2019, this study estimates that the imposition of VAT increases poverty and reduces the relatively small income level for consumption. In general, it estimates that the imposition of VAT in Indonesia will increase poverty, although it can reduce inequality. When receiving cash transfers, poverty and inequality decreased relatively small. These results imply that the fiscal policy of providing direct cash transfers is moderately effective in reducing poverty but not inequality.